Perbanyakan Anggrek Dendrobium ‘Gradita 31’melalui Embriogenesis Somatik - Hamiranti, Rahmadyah (Savana Cendana, 2024)
Dendrobium tissue culture through somatic embryogenesis process is a solution for mass propagation. The concentration of PGR and the composition of basic media are important factors in somatic embryogenesis. This research aimed to obtain the best type of basic media and BA concentration for regeneration process through somatic embryogenesis on Dendrobium 'Gradita 31' orchid. This research used a completely randomized design with 3 replications arranged factorial. The first factor was the type of basic media, ½ MS and MS. The second factor was concentration of cytokinin BA 1, 2 and 3 mg/L combined with NAA 0.5 mg/L. Each experimental unit consisted of 2 culture bottles, each contained 2 explants. The data from each variable was analyzed using analysis of variance, and continued with the BNJ test at a significance level of 0,05. The results of the research showed that the type of basic media had no significant effect on all variables. Concentration 2 mg/L of BA gave the highest response to the variables of percentage of somatic embryo formation, number of SE per explant and number of shoots per clump.